EXPLORING THE ANTIOXIDANT ACTIVITY OF Eugenia uniflora L. EXTRACTS: A COMPARATIVE APPROACH BY DIFFERENT TECHNIQUES - Vinicius Monteiro Schaffka; Cássia Gonçalves Magalhães; Romaiana Picada Pereira (Química Nova)
Eugenia uniflora L (EU), Myrtaceae, known as pitangueira, is recognized as a source of bioactive compounds, mainly polyphenols. Considering the complexity and variety of factors that influence the composition of their extracts, assigning antioxidant properties to specimens from distinct locations and environmental conditions is important. In this study, the composition profile (total phenolic content (TPC), total flavonoid content (TFC), gas chromatography-mass spectrometry (GC-MS), and ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) fingerprint) and antioxidant activity (by chelating effect, phosphomolybdenum, 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), hypochlorous acid (HOCl), ferric reducing antioxidant power (FRAP), and cupric reducing antioxidant capacity (CUPRAC) assays) of the extracts from three specimens of pitangueira (EU1, EU2, and EU3) obtained at different pH values were compared. The results indicated that extracts obtained with ethyl acetate (EA) at pH 4 had the highest effectiveness due to their elevated levels of phenolic compounds. Additionally, a significant occurrence of flavonoids in EU2 was observed, as demonstrated by the antioxidant activity of EA at pH 8 and EA/MeOH (1:3). This study provides valuable insights into the chemical variability of E. uniflora and its significant impact on antioxidant activities, highlighting the importance of extraction conditions to enhance the therapeutic efficacy of its bioactive compounds.